Telangana people's struggle and its lessons - Sundarayya, P. (Delhi, 2006)
Few people, even within the Communist movement, can reflect on the Telangana People's Struggle with the acuity and eloquence that Sundarayya brings to bear in recounting the halcyon days of armed uprising and resistance. Sundarayya is privileged to do so, not only from the position of his close involvement as one of the leading organisers and underground activists of the period, but also from the leadership positions that he occupied within the Communist Party, that afforded an understanding and analysis that located the struggle within a wider ideological canvas. Divested of academic predilections, the book provides an insightful and authentic narration of a little documented struggle through the eyes of an individual privy to the intimate details, the thrusts and the parries, the successes and the shortcomings of a unique movement.
Keywords: Political movement-Telangana